2015
DOI: 10.1007/s00380-015-0777-7
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin use and incidence of stroke in Japanese hemodialysis patients with atrial fibrillation

Abstract: Atrial fibrillation (AF) is one of the major risk factor for ischemic stroke, and oral anticoagulation is generally indicated for prevention of stroke. However, the utility of oral anticoagulation for AF in dialysis patients remains controversial. In this single-center, retrospective, observational study, data from 1120 patients on maintenance hemodialysis were analyzed. Baseline medical data were collected from dialysis records including age, gender, the cause of end-stage renal disease, dialysis vintage, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 19 publications
0
37
1
1
Order By: Relevance
“…In the first pass, 2139 articles (after removal of duplicates, n = 218) were screened against the inclusion and exclusion criteria based on the screening of the title and abstract. Finally, only 15 articles 2,4,7,8,11,12,[29][30][31][32][33][34][35][36][37] were qualified for inclusion in the meta-analysis after a full-text screening of the articles in the second pass. We found two retrospective cohort studies by Tan et al 3,33 using US Renal Data System.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first pass, 2139 articles (after removal of duplicates, n = 218) were screened against the inclusion and exclusion criteria based on the screening of the title and abstract. Finally, only 15 articles 2,4,7,8,11,12,[29][30][31][32][33][34][35][36][37] were qualified for inclusion in the meta-analysis after a full-text screening of the articles in the second pass. We found two retrospective cohort studies by Tan et al 3,33 using US Renal Data System.…”
Section: Resultsmentioning
confidence: 99%
“…All the included studies were a cohort in nature, of which 12 were retrospective cohort 2,4,7,8,[29][30][31][32][33][35][36][37] and three were prospective cohort studies. 11,12,34 This meta-analysis compromised of 53 581 patients of whom 17 469 patients were on warfarin.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the observational nature of cohort studies, all 20 included studies had at least an overall rating of moderate risk of bias: 5 studies were rated as moderate [ 22 , 25 28 ]; 7 studies were rated as serious [ 13 , 14 , 20 , 23 , 24 , 30 , 31 ]; 8 studies were rated as having a critical risk of bias [ 14 16 , 21 , 29 , 32 – 35 ] (Table 2 , Appendix Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Compared to previously published systematic reviews [ 7 10 ], our review included several studies recently published [ 15 , 16 , 35 ] and expanded the study population to include PD [ 21 ] and stage 5 CKD [ 25 ], which were not included in these reviews [ 7 9 , 36 ]. Our pooled estimate of ischemic stroke and bleeding outcomes were consistent in direction and magnitude with those reported by Li et al, Liu et al and Dahal et al [ 7 , 8 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated greater than 2‐fold increased risk of stroke in patients 75 or older . Several other small studies between 2011 and 2016 demonstrated no benefit in terms of mortality or stroke or thromboembolism prevention …”
Section: Management By Ckd Stagementioning
confidence: 99%